A case report of myocardial infarction with non-obstructive coronary arteries as the initial presentation of eosinophilic granulomatosis with polyangiitis. Issue 1 (19th January 2022) - Chatta, Payush; Park, Eunwoo; Ghatnekar, Nikhil; Kirk, Shannon; Hilliard, Anthony; Parwani, Purvi
Abstract: Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a multisystem disorder commonly affecting the lung and skin, with cardiovascular involvement found in up to 60% of patients. We present a case of myocardial infarction with non-obstructive coronary arteries (MINOCA) as the initial presentation of EGPA. Case summary: A 52-year-old female with past medical history of asthma, recurrent sinusitis, and peripheral neuropathy presented to our hospital with chest pain, rash, acute vision loss, elevated troponin, and peripheral eosinophilia. Electrocardiogram showed no ischaemic changes and coronary angiography displayed normal coronary anatomy. On a subsequent visit, cardiac magnetic resonance (CMR) showed predominant focal anteroseptal and inferoseptal akinesis with focal sub-endocardial delayed enhancement, indicative of a myocardial infarction involving the septal branches of the left anterior descending artery. Due to the focal findings on CMR, peripheral eosinophilia, and rash, the patient was evaluated for EGPA. Rheumatologic workup and skin biopsy were suggestive of small vessel vasculitis. The patient was diagnosed with multi-organ EGPA, involving the coronaries, which was ultimately thought to be the aetiology of her MINOCA. Following steroid and monoclonal antibody therapy, the patient experienced notable improvement in her cardiac function at follow-up appointments. Discussion: This is a unique case MINOCA as the initial presentation of EGPA. Considering the heterogeneous disease presentation of those diagnosed with MINOCA, utilization of CMR is essential to guide diagnosis and management of such patients.